Effects of orifice sizes for uncontrolled filling processes in water pipelines (2022)
The sizing of air valves during the air expulsion phase in rapid filling processes is crucial for design purposes. Mathematical models have been developed to simulate the behaviour of air valves during filling processes for air expulsion, utilising 1D and 2D schemes. These transient events involve the presence of two fluids with different properties and behaviours (water and air). The effect of air valves under scenarios of controlled filling processes has been studied by various authors; however, the analysis of uncontrolled filling processes using air valves has not yet been considered. In this scenario, water columns reach high velocities, causing part of them to close air valves, which generates an additional peak in air pocket pressure patterns. In this research, a two-dimensional computational fluid dynamics model is developed in OpenFOAM software to simulate the studied situations.